SLC2As as diagnostic markers and therapeutic targets in LUAD patients through bioinformatic analysis - Zhang, Yanli; Qin, Han; Bian, Jing; Ma, Zhanchuan; Yi, Huanfa (Frontiers in Pharmacology, 2022)
Facilitative glucose transporters (GLUTs), which are encoded by SLC2As, are responsible for mediating glucose absorption. In order to meet their higher energy demands, cancer cells are more likely than normal tissue cells to have elevated glucose transporters. Multiple pathogenic processes, such as cancer and immunological disorders, have been linked to GLUTs. Few studies, meanwhile, have been conducted on individuals with lung adenocarcinoma (LUAD) to evaluate all the 14 SLC2A genes. We first analyze increased protein levels of SLC2A1, SLC2A5, SLC2A6, SLC2A9 via HPA database and downregulated levels of SLC2A3, SLC2A6, SLC2A9, and SLC2A14 by ONCOMINE and UALCAN databases in patients with LUAD. Additionally, we found that lower levels of SLC2A3, SLC2A6, SLC2A9, SLC2A12, and SLC2A14 and higher levels of SLC2A1, SLC2A5, SLC2A10, and SLC2A11 have an association with advanced tumor stage. SLC2A1, SLC2A7, and SLC2A11 were identified as prognostic signature for LUAD. Kaplan-Meier analysis, Univariate Cox regression, multivariate Cox regression and ROC analyses further revealed that this 3 genes signature was a novel and important prognostic factor. Mechanistically, the aberrant expression of these molecules is caused, in part, by the hypomethylation and hypermethylation of SLC2A3, SLC2A10, and SLC2A14 by SLC2A1, SLC2A2, SLC2A5, SLC2A6, SLC2A7, and SLC2A11. Additionally, SLC2A3, SLC2A5, SLC2A6, SLC2A9, and SLC2A14 contribute to LUAD by positively modulating M2 macrophage and T cell fatigue. Finally, pathways involving SLC2A1/BUB1B/mitotic cell cycle, SLC2A5/CD86/ negative regulation of immune system process, SLC2A6/PLEK /lymphocyte activation, SLC2A9/ CD4/regulation of cytokine production may participate in the pathogenesis of LUAD. In summary, our results will provide the theoretical basis on SLC2As as diagnostic makers and therapeutic targets in LUAD.